A legislação brasileira na conservação das áreas úmidas - compilação de termos e definições - Caleffi, Vanessa (Universidade do Vale do Rio do Sinos, 2009)
This article aims to explore the wetlands, bringing its definition and identification, in addition to his duties and importance. A history to the laws involving this type of ecosystem is included in this work, together with the Brazilian laws, in federal and state level, focusing on areas of permanent preservation or conservation of wetlands. The main results of this study are found in the form of scientific article, supplemented with attachments where highlights the presence of a glossary of terms of wetlands. The final of the dissertation are based on results that provide important and additional allowances for the preservation of wetlands.
Keywords: conservação; definições; legislação; termos; áreas úmidas; conservation; definitions; legislation; terms; wetlands; Ciências Biológicas